Operationalisation of ESD Criteria for the Inventory of Out-of-School ESD Learning Places in Rhineland-Palatinate - Wittlich, Christian; Brühne , Thomas (Journal of Geography Education, 2022)
With the help of a multi-stage analysis, out-of-school places of learning in the Rhineland-Palatinate study area were recorded, which on the one hand show geological-expert references and on the other hand conceptual references to the ESD education concept. ESD criteria developed in-house were operationalised as a methodological instrument in the form of an ESD checklist for out-of-school places of learning in order to identify empirical resilience. The data obtained in this way provide the basis for the creation of a learning location database of out-of-school learning locations with ESD reference. A cartographic visualisation of the data shows the following spatial distribution pattern: In addition to districts and cities with well supplied ESD learning locations, real ESD learning location deserts coexist. Furthermore, there is an accumulation of ESD learning sites in areas close to forests. The digitisation of the learning place database could be a desirable research-oriented output for teachers in educational practice in the future.